2005
DOI: 10.1007/s00535-004-1526-3
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological roles of macrophage migration inhibitory factor in gastrointestinal, hepatic, and pancreatic disorders

Abstract: Macrophage migration inhibitory factor (MIF) is a unique protein, participating in inflammation, immune response, and cell growth. MIF was first discovered as a lymphokine involved in delayed hypersensitivity and various macrophage functions, including phagocytosis, spreading, and tumoricidal activity. It has been reported that MIF is associated with the pathogenesis of a variety of diseases. MIF expression was increased at inflammatory sites in diseases such as rheumatoid arthritis and glomerulonephritis. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 65 publications
0
18
0
Order By: Relevance
“…Excessive inflammatory reaction known as systemic inflammatory response syndrome complicated by multisystem organ failure is considered as a leading cause of death in early AP [3][4][5] . So far, the evaluation of the role of mononuclear cells in this phenomenon has been focused on the monocyte/macrophage system, indicating strong activation of this system [7,[30][31][32] .…”
Section: Discussionmentioning
confidence: 99%
“…Excessive inflammatory reaction known as systemic inflammatory response syndrome complicated by multisystem organ failure is considered as a leading cause of death in early AP [3][4][5] . So far, the evaluation of the role of mononuclear cells in this phenomenon has been focused on the monocyte/macrophage system, indicating strong activation of this system [7,[30][31][32] .…”
Section: Discussionmentioning
confidence: 99%
“…It participates in inflammation, immune response, and cell proliferation and differentiation. It has effects on the growth of tumor cells as well as non-tumor cells in the process of wound repair [20]. Experimental studies have reported that MIC-1 is expressed in various gastrointestinal tissues including the stomach, intestine, liver and pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] In addition, MIF is rather unique in that it possesses enzymatic tautomerase activity. [7][8][9] Although the physiological role for MIF's tautomerase activity remains to be discovered, blocking MIF's tautomerase activity can also block MIF's biological activity.…”
Section: Introductionmentioning
confidence: 99%